Analisis Kebutuhan Penyusunan Perangkat Pembelajaran Tematik Berbasis HOTS (Higher of Order Thinking Skills) pada Kurikulum 2013 di SD Muhammadiyah 05 Batu - Tyas Deviana; Dian Ika Kusumaningtyas (Universitas Muhammadiyah Enrekang, 2019)
The implementation of learning in SD Muhammadiyah 5 Batu is still new in implementing the 2013 curriculum. Related is also related to learning tools. The tools used by the teacher have not yet reached the level of HOTS (Higher of Order Thinking Skills) thinking ability as evidenced from the learning objectives in the RPP that are made only at the level 1 level (C1 - C2). Where the learning kit announces HOTS (Higher Level Thinking Skills) asking for learning activities in it to be synonymous with cognitive level 3 learning activities, namely at C4 - C6. The initial conditions in the field indicate that learning activities in the RPP are only cooperative learning and group discussions or class discussions, learning activities are less varied. Seeing the conditions that have been described, it is deemed necessary to further improve the analysis of HOTS-based device installation needs in K13. The analysis of the needs of the preparation of HOTS-based tools discusses curriculum analysis, student analysis, and analysis of field considerations. Analysis of some aspects that need to be done to study the description of the need to be developed in a learning application in the form of RPP based on HOTS that suits the needs of students, curriculum, and also the field. In addition, in order to obtain a complete and complete picture related to learning and learning tools in SD Muhammadiyah 5 Batu.